Innovation, Learning, and Communities - Häkkinen, Päivi (Human Technology, 2012)
Research in the interdisciplinary field of human–technology interaction takes many forms and perspectives. However, no matter which lens is used in evaluating the interrelationship between the human and the technology or which technology is being explored, issues of learning, context, use intention, and community form essential components of all research because they are components of all technology use. Of these four components, learning is affected by and affects the other three.